Penerapan Pembelajaran PAI Berbasis Highier Order Thinking Skill di SMA Negeri 1 Bluluk Lamongan - Fitriyah, Azzizah Lailatin; Lilawati, Emi (ISLAMIKA, 2024)
HOTS (Higher Order Thinking Skill) education can help develop student character. HOTS is a type of high-level rational ability in students, that is, high-level rationality with the intention to return to appropriate and creative work. This research aims: 1) To determine the planning and implementation of HOTS-based PAI learning for class XI 1 SMA N 1 Bluluk Lamongan students. 2) Knowing the evaluation of HOTS-based PAI learning for class XI 1 SMA N 1 Bluluk Lamongan students. The methodology used in this research is a qualitative approach using a descriptive research design. Three collection methods include observation, interviews, and documentation. The type and summary of data used is primary data and secondary data by analyzing data absorption techniques. Research findings show the use of HOTS materials for PAI which is carried out through observations and actions as well as evaluations carried out. The implementation of HOTS-based PAI in schools can increase students' ability to improve their high-level thinking abilities.